Para-narratives in the Odyssey : stories in the frame - Alden, Maureen (Oxford University Press, 2017)
'Para-Narratives in the Odyssey' is a full-length study in English of the function and significance of secondary 'para-narratives' in the poem and their relationship to its main story. Entertaining in their own right, they create illuminating parallels to their immediate context and enhance our understanding of the central narrative